Perbaikan Ketahanan Lifetime Bladder untuk Peningkatan Curing Efficiency pada Proses Industri Tire Manufacture - Tubagus Hendri Febriana; Herna Dewita; Cecep Hermawan; Hendi Herlambang (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2020)
The efficiency of the curing process is one of the critical points in the tire manufacturing industry. One of the factors that need to be considered in curing efficiency is the low age of the bladder as an auxiliary material used for heat / thermal transfer from the curing machine to green tires during the curing process. Low bladder life will directly impact the high frequency of bladder changes, leading to lost time in the preparation and assembly of the curing machine at the processing stage. In this condition, when studied, the average life span of the bladder in 2017 was 237 times used, while the company's target in 2018 for the bladder life target was set at 450 times to support the curing process efficiency project. This study aims to analyze the potential problems that cause a low shelf life. This research uses the concept of DMAIC (Define-Measure-Analyse-Improve-Control) and Failure Mode and Effect Analysis (FMEA) to determine the main causal factors and preventive actions and to determine priority improvements based on the Risk Priority Number (RPN). The improvement results showed that bladder life could increase from 237 times to 450 times as targeted, loss of bladder change during curing could reduce 0.79%, and index bladder consumption could be reduced by 36.7% total cost savings of USD 196,576 per year.